Divination. (3rd April 2018) - Robertson, Robin
Abstract : This article ranges widely over the meaning and underlying methods of divination. It begins with an examination of the shared belief systems of almost all psychics and sensitives, and the process by which they access divinatory material. I also discuss my workshops in which normal people experience some of the same divinatory abilities. The article then shifts to describe a wide variety of divinatory tools used throughout the world by people other than psychics, and speculates on the methods that underlie all these tools. These methods all seem to be based on extracting order from randomness either (1) through intuition or (2) from a structured, often numeric, method. The use of dreams is examined as one of the earliest methods of extracting divinatory information through intuition. Then numeric methods are examined in more detail. Finally, the I Ching is discussed in great detail as the most developed such numeric divinatory tool.